Black Power TV - Heitner, Devorah, 1975- (Book collections on Project MUSE., 2013)
In the wake of the King assassination and subsequent uprisings, Black Public Affairs Television emerged. Devorah Heitner tells its story, analyzing the production, reception, and content of its early groundbreaking programs.